A study of the effects of different group involvement on children’s sport behavioral choices: a group preference-based perspective - Fan, Xiaoyan; Xiao, Hui; Yang, Tongnian; Liu, Qi (Frontiers in Psychology, 2025)
IntroductionIn order to investigate the characteristics of children’s sport behavioral choices in different group-involvement contexts and the role of group favoritism in this relationship.Methods280 children aged 3–8 years were recruited for a psycho-experimental study in two different experimental contexts.Results and discussionThe results found that (1) in the in-group and out-group involvement situations, the rate of physical activity selection was significantly higher in the in-group than in the out-group, and there was a significant difference, indicating that there was an in-group preference in the selection of physical activities by children aged 3 to 8 years old. (2) There was a significant age difference in the low favorite physical activity choice in the parent-intimate peer involvement context. Negative rank was lower than positive rank in physical activity choice among 3- to 4- and 5- to 6-years-olds, suggesting the presence of parental attachment behaviors among 3- to 4- and 5- to 6-years-olds. In summary, it can be seen that children aged 3–8 years show a clear phenomenon of in-group favoritism in their choice of physical activity, which may be related to children’s early social cognitive development and attachment behavior.